Language Kinship of Wooi, Poom, Ansus, and Ambai in Yapen, Papua - Nuraeni, Neni; Hendrokumoro, Hendrokumoro (Deskripsi Bahasa, 2024)
This study aims to determine the language kinship in Wooi, Poom, Ansus, and Ambai languages. Data were collected from an interview with the indigenous speakers of Wooi, Poom, Ansus, and Ambai languages. This research employed a historical-comparative linguistics approach, which is the lexicostatistics and glottochronology method. Data were in the form of 200 basic vocabularies and were calculated with lexicostatistics and glottochronology formula. These research findings indicate the 64% language kinship between Wooi and Ansus. That result is the highest percentage of language kinship between the four languages. 54% is between Wooi and Poom. 53% is between Ansus and Ambai. 49% is between Ansus and Poom. 45% is between Wooi and Ambai. And 35% is between Poom and Ambai, which is the lowest percentage of language kinship. Thus, this study proves that Wooi, Poom, and Ansus are the languages classified into a family. Wooi, Ansus, and Ambai are also the languages classified into a family. Meanwhile, Poom and Ambai are classified as stock.